Therapeutic Drug Monitoring in Pharmacovigilance and Pharmacotherapy Safety - Haen, E. (Pharmacopsychiatry, 2011)
Quantification of serum or plasma concentrations of medications is essential to find out if an adverse drug effect (ADE) is associated with an elevated drug concentration. In former years TDM was therefore often used in pharmacovigilance just to confirm that an ADE that had already occurred was due to an elevated drug plasma concentration without identifying the underlying cause for the surprising high concentration. This old approach of Therapeutic Drug Monitoring (TDM) in pharmacovigilance needs to be revised due to new developments in information technology, new analytical procedures and due to the inclusion of clinical pharmacological expert opinions in the presentation of laboratory medicine results. Today, TDM may be used to prevent ADE, rather than just confirming a suggested cause of an ADE that has happened in the past. This approach means that blood should be drawn for TDM analysis after the pharmacokinetic steady state has been reached (5 times of the elimination half life of the drug) with low to moderate dosages under the intended (poly)medication if the patient is clinically regarded as not belonging to the “normal” patient population. With the availability of reliable automated analytical methods this can be performed at a reasonable price. Funds may be saved to the health care system, because hospitalization will be thereby shortened and expensive diagnoses and treatment of ADE will be avoided. However, this has still to be proven in cross-system studies: Budget will be saved in 2 areas of the health system (hospital stay and drug costs), whereas a much smaller amount of money has to be invested for laboratory analyses in another area. TDM may thus change pharmacovigilance as a tool for monitoring and documentation of ADE to a safety tool in drug therapy for prevention of ADE.
Keywords: TDM; pharmacovigilance; drug safety; pharmacotherapy safety; dose-related reference range; therapeutic reference range; KONBEST; laboratory information management system (LIMS); 9-field board; clinical pharmacological comment; HPLC; UHPLC; quantification of drug concentration; analytical methods